The path as facilitators of the Alternative to Violence Program of students deprived of liberty at CAI, Jorge Debravo - Romero Alvarado, José Daniel; Rivera Pereira, Gabriela Rivera (Scientific journal of social studies, 2025)
The Alternative to Violence Program (AVP) in Costa Rica has been implemented since the 1990s thanks to the Center for Peace Studies Foundation, with the purpose of promoting a more peaceful society. The AVP uses a participatory methodology focused on issues such as self-esteem, cooperation and conflict management, enabling people to transform their lives and their environment. An important milestone was the training of students deprived of their liberty to become AVP facilitators. Thanks to the collaboration with the UNED Student Ombudsman's Office, in December 2023, a group of inmates from the CAI Jorge Debravo were enrolled in the basic module of the program. Subsequently, in March 2024, they received training as facilitators, and in July 2024 they delivered their first training, marking a historic event. This article highlights the transformative capacity of the AVP, demonstrating that change is possible, even for those who have lived in contexts of violence.
Keywords: Peace Education; prisoners; facilitators; conflict resolution; participatory methodology